2015
DOI: 10.1186/s13104-015-1587-9
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-reported height and weight for estimating prevalence of overweight among Estonian adolescents: the Health Behaviour in School-aged Children study

Abstract: BackgroundLow to moderate agreement between self-reported and directly measured anthropometry is shown in studies for adults and children. However, this issue needs further evaluation during puberty, a period marked by several transitions. We examined the correspondence of BMI status based on self-reported versus measured anthropometric data among Estonian adolescents with a specific focus on gender and age differences.MethodsSelf-reported height and weight were determined in a national representative sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 36 publications
4
58
1
1
Order By: Relevance
“…There was a higher prevalence of thinness grade 2 among girls, between 2.6% and 3.3% in 2006, compared with the present study . This could have been an effect of self‐reported data, which has been shown to overestimate the prevalence of thinness in this age group . There were not any significant changes in the prevalence of thinness in the Health Behaviour in School‐aged Children study between 1998 and 2006 .…”
Section: Discussioncontrasting
confidence: 73%
“…There was a higher prevalence of thinness grade 2 among girls, between 2.6% and 3.3% in 2006, compared with the present study . This could have been an effect of self‐reported data, which has been shown to overestimate the prevalence of thinness in this age group . There were not any significant changes in the prevalence of thinness in the Health Behaviour in School‐aged Children study between 1998 and 2006 .…”
Section: Discussioncontrasting
confidence: 73%
“…With this in mind, once cases of biologically implausible data were removed, rates of overweight and obesity in this sample were comparable with national samples of 15.2% overweight and 5.5% obese (4–5 years of age), although rates of underweight appear to be over‐represented compared with national data (22.4% vs. 7.55%, respectively) . Similar to what has been reported in other studies, anthropometric data deemed biologically implausible were higher in boys, although, contrary to other studies, implausible data were higher in younger children . No differences in demographic characteristics were seen between children classified as underweight compared with other BMI categories.…”
Section: Discussionmentioning
confidence: 99%
“…In a US study, this trend was reported only among female adolescents [27]. On the contrary, in a study among Estonian adolescents, the trend was in the opposite direction, with more accurate self-reporting by older adolescents [28]. In addition, Jayawardene and colleagues [25] analysed data from the 2010 US National Youth Physical Activity and Nutrition Survey which showed that US adolescents who were obese or were trying to lose weight tended to under-report their weight, and consequently underestimated their BMI.…”
Section: Discussionmentioning
confidence: 99%